Assessing the relaxation of recycled aggregates concrete from free and restrained shrinkage tests. (1st April 2023) - Roziere, Emmanuel; Bendimerad, Ahmed Z.; Samouh, Hamza; Loukili, Ahmed
Abstract: Recycled concrete aggregates (RCA) lead to higher shrinkage of concrete than natural aggregates because of two main reasons: lower elastic modulus and possible shrinkage of RCA. The study aims at quantifying the effects of both phenomena, thus Trisphere model has been chosen as it takes into account the influence of aggregates modulus and shrinkage on the properties of concrete. The existing model has been adapted to determine the elastic modulus and shrinkage of recycled aggregates from the modulus and shrinkage of concrete. The shrinkage of coarse RCA was much lower than the shrinkage of fine RCA, thus the increase in the shrinkage of concrete can be mainly attributed to the reduction in aggregate modulus and variations of composition parameters (W/C, volume of paste). The model also allows estimating the delayed elastic modulus of concrete. The obtained values are compared with the numerical determination of viscoelastic-aging Young's modulus from restrained shrinkage tests (ring tests). The long-term moduli provided by both approaches are consistent for most of studied materials. The relaxation increased with the content of coarse recycled aggregates, but the variation was lower than reported in creep studies. This could be due to lower relative stress level as recycled aggregates also induce lower elastic modulus thus lower stress for a given restraint. Highlights: Free and restrained shrinkage of concrete with recycled concrete aggregates (RCA). Elastic modulus and shrinkage of RCA determined from the properties of new concrete. Adapted Trisphere model used to provide the delayed elastic modulus of concrete. Numerical determination of viscoelastic-aging Young's modulus from ring tests. Good correlation between long-term moduli provided by both approaches.